The Effect of Diabetic Patients with Chronic Periodontitis on Serum Paraoxonase, Adenosine Deaminase (Mustansiria Dental Journal, 2018)
Diabetes mellitus is a major global health problem and represents a risk factor forperiodontitis. This study was carried out to determine the Paraoxonase (PON),adenosine deaminase (ADA), aspartate and alanine aminotransferase (AST, ALT),lactate dehydrogenase (LDH) activity in diabetic patients with Periodontitis.This study was carried out on nineteen diabetic patients (25–50 years),) withgeneralized moderate-to-severe periodontitis were selected based on periodontalparameters of gingival index (GI), probing pocket depth (PPD), clinicalattachment level (CAL) and radiographic parameters. As well as 19 healthy agematchedcontrol participants. Data were evaluated using descriptive statistics, ttest,Chi-Square.Results: Obtained results were shown statistically significant increases of activity ofADA, LDH, AST, and ALT, while PON concentration decreased in saliva fromdiabetic patients with periodontal disease in relation to control group.Conclusion: In patients with advanced periodontitis, the salivary PON, level weresignificantly lower whereas ADA higher compared to healthy individuals. Thus,assessment of salivary leptin can be done as a non-invasive and simple method todetermine the susceptibility of patients to advanced periodontitis.